Application of Good Governance Principles and Inhibiting Factors to the Implementation of Village Government in Pujut Village Central Lombok Regency - Awaludin; Nurjayadi (PALAR | PAKUAN LAW REVIEW, 2026)
Law Number 6 of 2014 concerning Villages, will undergo the last amendment in 2024, through Law Number 3 of 2024 concerning the second amendment to Law Number 6 of 2014 concerning Villages. The changes aim to strengthen the implementation of the principles of Good Governance at the village level, improve the professionalism of village officials, and ensure transparency, accountability, community participation, the rule of law and justice in the development and management of the village budget. However, in practice, there are still many challenges and obstacles in the application of Good Governance principles, such as; Limited community participation, transparency in village budget management, effectiveness of village apparatus performance, and justice for residents, as well as rule of law for the community. The research used is empirical legal research. In this study, the compiler uses a statutory approach (statute approach) and a conceptual approach and an emppris approach. Judging from Article 24 of Law Number 3 of 2024 concerning Villages, the implementation of good governance principles in villages is not going well. Participation in village government is not carried out with the spirit of kinship and mutual cooperation so that criticism and suggestions cannot be done properly. Likewise with transparency and accountability, accountability reports made by the village government are not only submitted to the district/central government, but also informed to the community. Keywords : Good Governance, Village Government.